Anisotropic compressive deformation behavior of hot-rolled Mg-3Al-0.5Ce alloy - Prakash C. Gautam; Somjeet Biswas (Journal of Magnesium and Alloys)
This work investigates the anisotropic compressive deformation of hot-rolled Mg-3Al-0.5Ce alloy and correlates it with microstructure and texture. Hot-rolled alloy had elongated and equiaxed grains with long-aligned Al11Ce3 precipitates within the grain boundaries along rolling direction (RD) and basal texture along normal direction (ND). Analytical and crystal plasticity-based viscoplastic self-consistent predominant twin reorientation (VPSC-PTR) approaches were employed to simulate the flow curve and texture evolution for deeper insight into the deformation behavior. For compression direction (CD)∥to RD and transverse direction (TD), the basal texture was ∼⊥ to CD, which favored {101¯2}〈101¯1〉 extension twins (ET). The ETs nucleate, broaden and engulf the parent matrices with strain, rotating the lattice by ∼86.4∘ about 〈21¯1¯0〉 axes to a geometrically hard orientation with c-axis ∼∥toCD, leading to sigmoidal flow and increasing stage-II strain hardening rate (SHR). However, Al11Ce3 weakened the basal texture intensity, reducing the stage-II strain hardening compared to the single-phase Mg alloy investigated earlier. The presence of Al11Ce3 intermetallics delayed the ET nucleation event, which initiates at ε∼0.018. The ET fraction evolves to ∼0.85, lower than in the previous works on single phase Mg alloy. A reduction in the +ve SHR slope could be observed from ε = 0.03 to 0.06, indicating increased slip activities in this portion of stage-II. Beyond ε = 0.1, decreasing stage-III SHR was observed due to basal 〈a〉, and pyr 〈c + a〉-I and II slip activities in the ET orientation. The difference in the compressive behavior along RD and TD could not be observed due to Al11Ce3 precipitate's morphology with elongation along RD. For CD∥to ND, the compressive flow behavior was parabolic with decreasing SHR due to slip-based deformation. ET didn't form, and the texture change was negligible, with initial and final textures having basal texture ∼∥toCD, the geometrically hard orientation.